2012
DOI: 10.21825/af.v25i2.4953
|View full text |Cite
|
Sign up to set email alerts
|

Norms, self-interest and effectiveness: explaining double standards in EU reactions to violations of democratic principles in Sub-Saharan Africa

Abstract: The promotion of democracy has become a key objective of the European Union (EU) in sub-Saharan Africa.One of the ways in which this objective is pursued is by reacting to violations of democratic principles using negative measures: naming and shaming strategies or economic/diplomatic sanctions. Yet the application of negative measures has been criticised as being characterised by "double standards", meaning that similar violations of democratic principles have led to a different response from the EU. This dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 216 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…This asserts an explanation of the EU foreign and security policy as a response to systemic changes in the distribution of global power, combined with the use of the EU policy instruments by its member states as a means to further their own national interests. These theoretical debates have been applied to the EU political conditionality policies by Del Biondo (2015Biondo ( , 2012Biondo ( , 2011 in her consideration of the factors that account for the (non-)implementation of aid sanctions in the context of the EU's relations with the African, Caribbean and Pacific (ACP) group of nations, with the finding that the EU's own interests generally trumped democracy in sub-Saharan Africa. There was usually an absence of the EU interests in those country cases where conditionality and sanctions were applied, while the EU measures were limited to 'rhetorical action' only where interests existed (Del Biondo 2015: 77).…”
Section: Political Conditionality In the 1990s And Changes To The Aid...mentioning
confidence: 99%
See 2 more Smart Citations
“…This asserts an explanation of the EU foreign and security policy as a response to systemic changes in the distribution of global power, combined with the use of the EU policy instruments by its member states as a means to further their own national interests. These theoretical debates have been applied to the EU political conditionality policies by Del Biondo (2015Biondo ( , 2012Biondo ( , 2011 in her consideration of the factors that account for the (non-)implementation of aid sanctions in the context of the EU's relations with the African, Caribbean and Pacific (ACP) group of nations, with the finding that the EU's own interests generally trumped democracy in sub-Saharan Africa. There was usually an absence of the EU interests in those country cases where conditionality and sanctions were applied, while the EU measures were limited to 'rhetorical action' only where interests existed (Del Biondo 2015: 77).…”
Section: Political Conditionality In the 1990s And Changes To The Aid...mentioning
confidence: 99%
“…While the prioritisation of such self-interests over issues of human rights and democracy may be an element of continuity in donors' policy practice, have there been changes in the respective significance of different aspects of self-interest? Earlier research on aid sanctions found that commercial interests were dominant (Del Biondo 2012, Crawford 2001, with such economic interests also confirmed as key to aid distribution and the size of aid allocations in the late 1980s and 1990s (Schraeder et al 1998: 321-22). But has this changed and have security interests now overtaken other competing interests as the dominant form of self-interest that trumps political conditionality, and, if so, what explains such change?…”
Section: Political Conditionality In the 1990s And Changes To The Aid...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, Karen Del Biondo provides evidence that there have been double standards in the EU's reactions to the violations of democratic principles in 10 African countries. The similar violations of democratic principles by Eritrea, Ethiopia, Kenya, Chad, Niger, Nigeria, Rwanda, Guinea, Côte d'Ivoire, and Zimbabwe received dissimilar reactions to protect the self-interested objectives of the EU [135]. An up-to-date example of the international corruption according to my suggested definition is the intervention of USA and several European countries to suppress the Arab Spring revolutions.…”
Section: The International System Levelmentioning
confidence: 97%
“…They are: the primacy of economic interests, the primacy of security interests, and special relationships related to colonial history. Some literature (Saltnes, 2013;Del Biondo, 2011, 2012 relate the Ethiopia case to the second argument, as the country has a very weak economy and no ties with any of the former colonizing countries of Europe. Del Biondo (2011, p. 386) argues that Ethiopia is a trusted ally of the EU in the Horn of Africa because of its relative stability in the unstable region.…”
Section: Why Does the Eu Tolerate Ethiopia?mentioning
confidence: 99%